Political Behavior of the Chinese Ethnic Community in the 2024 Legislative Election in Lhokseumawe City - Fitri, Amanda; Muzaffarsyah, Teuku; Zulhilmi, Zulhilmi; Faisal, Naidi; Zulham, Zulham (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This study examines the political behavior of the Chinese ethnic community in Lhokseumawe, Aceh, during the 2024 Legislative Election. The research explores how this minority group participates in politics and what factors shape its voting decisions within a post-conflict environment. A qualitative descriptive approach was applied, using in-depth interviews, participant observation, and document analysis conducted between April and May 2025. Ten informants were selected through purposive and snowball sampling, representing community leaders, business actors, first-time voters, and a local academic. The findings show that participation among the Chinese community is active in the formal sense but limited in scope. Voting is treated as a civic responsibility, while involvement in party or campaign activities is minimal. Economic considerations are the strongest influence on political choice, as respondents associate stable governance with the continuity of their businesses. Family and community networks play a guiding role in decision-making, and national parties are preferred for their perceived neutrality and inclusiveness. These orientations produce a pattern of political behavior that values stability and social harmony over ideological alignment or power competition. Interpreted through the lens of rational choice and social identity theories, the findings suggest that political participation among this minority group reflects a pragmatic adaptation to local conditions. Engagement in electoral processes serves as both an affirmation of citizenship and a strategy to maintain coexistence within a socially sensitive environment. The study provides insight into how small ethnic minorities in post-conflict areas negotiate democratic participation through cautious and context-aware practices.